STUDI KRITIS HUKUM WASILAH MAKSIAT - Kholid Saifulloh (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2019)
Every Muslim is certainly afraid to commit immorality to Allah subhanahu wa ta'ala, because he is aware that all forms of disobedience to Him are sin. However, sometimes the act done by someone is unwittingly has the potential to give birth to immorality. On the one hand, maybe the person is not aware of this potential; because basically there is no intention of him at all to act. But on the other hand, those who witnessed this saw that disobedience was the result of that action, so they were motivated to do the same thing, especially those who indeed wanted the immorality from the beginning. This paper examines thoroughly the laws relating to cases that have the potential to become immoral immorality.